2002
DOI: 10.2166/wst.2002.0138
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and water quality monitoring in the Golden Horn

Abstract: In this work, the oceanographic aspects of the Golden Horn and some results of the Golden Horn Rehabilitation Project are presented. The hydrographic structure of the Golden Horn responds rapidly to the conditions in the southern Bosphorus, which is especially true for the outer parts of the estuary up to the Valide Sultan Bridge (VS). West of this bridge which was blocked by the pontoons of the bridge, carries the major pollution load and is dependent on the underlying water and surface mixing, for its renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Precipitation, which increases terrestrial runoffs, has appeared as the most important factor affecting nutrient concentrations in the GHE in recent decades (Sur et al, 2002). High nutrient concentrations in the upper estuary during rainy periods indicated that this area has an even higher risk of pollution compared to the rest of the estuary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation, which increases terrestrial runoffs, has appeared as the most important factor affecting nutrient concentrations in the GHE in recent decades (Sur et al, 2002). High nutrient concentrations in the upper estuary during rainy periods indicated that this area has an even higher risk of pollution compared to the rest of the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum depth is 40 m in the lower part, rapidly decreasing to 14 m in the middle part and to <4 m in the upper part, where two small streams (Alibey and Kağıthane) carry freshwater into the estuary. Following the construction of a series of dams on these streams, freshwater input considerably decreased and precipitation has become the main source of variability in freshwater for the GHE (Sur et al, 2002). The lower part of the GHE is characterized by a two-layered structure similar to the neighboring Strait of Istanbul, where the upper layer flowing from the Black Sea has a salinity of ~18 and the lower layer flowing from the Mediterranean Sea has a salinity of ~38.…”
Section: Study Area and Sampling Strategymentioning
confidence: 99%
“…Although the two streams as known Alibey and Kağıthane carry freshwater to the GHE, the amount of the water runoff is generally low. Therefore, the main source of the freshwater flowing into the GHE is rainfall (Sur et al 2002). The LE is characterized by a two-layered structure similar to the neighboring Strait of Istanbul where upper layer waters has a salinity of ∼18 psu, originated from Black Sea and lower layer waters has a salinity of ∼38 psu, originated from the Mediterranean Sea.…”
Section: Study Areamentioning
confidence: 99%
“…The maximum depth of the estuary is around 15 m in mid-estuary and 4-5 m in the upper parts. The main source of the freshwater flowing into the Golden Horn is rainfall (Sur et al, 2002).…”
Section: Introductionmentioning
confidence: 99%